Diversity studies in 21 maize (Zea mays L.) accessions based on agro-morphological characters and diversity array technology (DArTs) - Nwogwugwu, P.A. (Federal University of Agriculture, Abeokuta, 2023)
Maize (Zea mays L.) is one of the most important crops in the world, being among the main sources of human food, animal feed, and industrial raw material. Landraces have certain genetic integrity, which is recognizable morphologically and by farmers. Maize grain yield is influenced by environmental conditions that can either boost production or retard its development, hence the need to determine the enormous genetic diversity in maize and identify accessions with good adaptability in contrasting environments for optimum yield. This study determined the genetic diversity in twenty-one accessions of Maize based on agro-morphological characters and Diversity Array Technology Sequence (DArTseq). Twenty-one maize accessions from different parts of the countries and one check variety were evaluated under growing conditions at the International Institute of Tropical Agriculture (IITA), Ibadan (Latitude 7.49oN, Longitude 3.89oE and altitude 239.34 m above sea level, IITA, Ikenne (Lat 12°16′N and Long 6°33′E) Federal University of Agriculture, Abeokuta (FUNAAB), Nigeria. (Lat. 70°15'N and Long. 30°25'E altitude 144 m above sea level) Ogun State. Laboratory work was carried out at the Bioscience Centre, IITA. The experiments were laid out in a Randomized Complete Block Design in three replicates at each location. Data collected were subjected to Analysis of Variance. Young leaf samples were collected from each accessions and used for DNA extraction, following standard procedures standard procedure. Whole-genome sequencing was carried out using Diversity Arrays Technology Sequence Single Nucleotide Polymorphic (DArTseq SNP) markers. The discovered DArTseq SNP markers. The discovered DArTseq SNP markers were aligned on the maize reference genome. The results showed that 80% of the total variation was explained by the first four principal components. PCI, PC2, and PC3 accounted for 51%, 67%, and 74% of the total variation with eigenvalues, ranging from 8.1, 0.67, and 0.7 respectively. Accession SUWAN-1-SR performed above average across the three locations. Accessions Tzm-1543, Tzm-1508, and Tzm-1534 were the most stable and high yielding across the three environments. Accessions TZM-1285, Tzm-1299 and Tzm-1543 were more adapted to Abeokuta. The accession was grouped into two clusters using DArTseq SNP markers. Out of 33629 SNPs discovered all over the maize reference. Only 169001 SNPs were retained after filtering, they were distributed all over the chromosomes of maize. The PCA based on (DArTseq) SNPs revealed that 18.8, 7.0, and 4.4% of genetic variance, was explained by the first, second, and third components, which assisted in grouping the maize accessions, based on the origin and status. The study concluded that three locations indicate the possibility of selecting maize from each accession with a high-yielding character. Accession Tzm-96, which is the most stable with a high yield, is recommended for large cultivation in Abeokuta, while the use of materials from different geographical origins is recommended for the breeding program.